(untitled) (CIPEEX, 2025)
Introduction: Damage control orthopedics (DCO) is a strategy used in surgeries with polytrauma patients, especially those with multiple injuries. It involves using temporary measures to quickly stabilize long bone fractures, perform pelvic mechanical compression, skeletal traction, and fracture fixation. The study compares two main approaches: DCO and early total care (ETC), promoting discussion of the clinical and laboratory criteria that guide medical decision-making. Objective: This study aims to enhance the understanding of trauma management through featured articles in the Journal of Trauma and Acute Care Surgery, with a focus on improving patient care and providing healthcare professionals with more information. Methods: The study is a narrative review of the literature on DCO in multiple trauma, providing a critical synthesis and update based on existing evidence, including international consensus and clinical experience. Results: The research highlights the need for a better understanding of the stress responses of trauma patients in order to reduce complication rates and suggests new treatment opportunities based on each patient’s physiological tolerance to injury. It emphasizes that ETC allows for a more individualized approach to the individual. In addition, the article proposes an algorithm based on each patient’s state of recovery in order to divide them and thus recommend the most appropriate course of action. Conclusions: It is concluded that the decision between using DCO or ETC in polytrauma patients should be guided by the patient’s state of recovery, and not only by the severity of bone trauma. In summary, the ideal orthopedic management in multiple trauma is individualized, dynamic, and multidisciplinary, prioritizing patient stability to reduce complications and provide better results.